DEFINING THE RISKS OF CONTAMINANT EXPOSURE TO PELAGIC SPECIES IN A SHIPPING CHANNEL - Cristina G.B. La; Kara E.Huff Hartz; Nick M. Hettel; Giovanni S. Molinari; Emerson Feddor; Shawn Acuña; Jacob Stagg; Amelie Segarra; Michael J. Lydy (Environmental Pollution, 2026)

Tracking pesticide accumulation in juvenile Chinook Salmon during outmigration through the Sacramento-San Joaquin River Delta - Hadis Miraly; S.D.M. Chinthaka; Kara E.Huff Hartz; Jacob Stagg; Shawn Acuña; Gregory Whitledge; Louise Cominassi; Amelie Segarra; Nann A. Fangue; Richard E. Connon; Michael J. Lydy (Environmental Pollution, 2026)

Practical Guide to Measuring Wetland Carbon Pools and Fluxes - Sheel Bansal; Irena F. Creed; Brian A. Tangen; Scott D. Bridgham; Ankur R. Desai; Ken W. Krauss; Scott C. Neubauer; Gregory B. Noe; Donald O. Rosenberry; Carl Trettin; Kimberly P. Wickland; Scott T. Allen; et al. (Wetlands, 2023)
Wetlands cover a small portion of the world, but have disproportionate influence on global carbon (C) sequestration, carbon dioxide and methane emissions, and aquatic C fluxes. However, the underlying biogeochemical processes that affect wetland C pools and fluxes are complex and dynamic, making measurements of wetland C challenging. Over decades of research, many observational, experimental, and analytical approaches have been developed to understand and quantify pools and fluxes of wetland C. Sampling approaches range in their representation of wetland C from short to long timeframes and local to landscape spatial scales. This review summarizes common and cutting-edge methodological approaches for quantifying wetland C pools and fluxes. We first define each of the major C pools and fluxes and provide rationale for their importance to wetland C dynamics. For each approach, we clarify what component of wetland C is measured and its spatial and temporal representativeness and constraints. We describe practical considerations for each approach, such as where and when an approach is typically used, who can conduct the measurements (expertise, training requirements), and how approaches are conducted, including considerations on equipment complexity and costs. Finally, we review key covariates and ancillary measurements that enhance the interpretation of findings and facilitate model development. The protocols that we describe to measure soil, water, vegetation, and gases are also relevant for related disciplines such as ecology. Improved quality and consistency of data collection and reporting across studies will help reduce global uncertainties and develop management strategies to use wetlands as nature-based climate solutions.